(3CSS YdejI hJLGQH YQHjIs - (3UHQi(B, (3YHO GdSejYs ((3GdbGgQI(B:s (3efThQGJ GdYQHjI ddJfejI GdEOGQjI(B,s, 2006)
(3Gdeaghe GdYdej ddJShjb(B- (3Gdeaghe GdYdej ddJShjb GdSjGMj(B- (3CShGb GdSjGMI(B- (3GdeSJgdc GdSjGMj(B- (3GdYQV GdSjGMj(B- (3JLGQH HYV GdOhd GdYQHjI aj GdJShjb GdSjGMj(B- (3GdeRjL GdJShjbj GdSjGMj(B- (3CSGSjGJ GdJShjb GdSjGMj(B- (3GSJQGJjLjGJ GdJShjb GdSjGMj(B- (3Gdeaghe GdYdej ddJShjb GdafObj(B- (3GdEJLGgGJ GdMOjKI aj GdJShjb GdSjGMj(B.s
Keywords: (3GdJShjb GdSjGMjs; (3GdJShjb GdafObjs